Listeria monocytogenes, a model in infection biology. (17th March 2020) - Lecuit, Marc
Abstract: Listeria monocytogenes causes listeriosis, a systemic infection which manifests as bacteremia, often complicated by meningoencephalitis in immunocompromised individuals and the elderly, and fetal‐placental infection in pregnant women. It has emerged over the past decades as a major foodborne pathogen, responsible for numerous outbreaks in Western countries, and more recently in Africa. L. monocytogenes ' pathogenic properties have been studied in detail, thanks to concomitant advances in biological sciences, in particular molecular biology, cell biology and immunology. L. monocytogenes has also been instrumental to basic advances in life sciences. L. monocytogenes therefore stands both a tool to understand biology and a model in infection biology. This review briefly summarises the clinical and some of the pathophysiological features of listeriosis. In the context of this special issue, it highlights some of the major discoveries made by Pascale Cossart in the fields of molecular and cellular microbiology since the mid‐eighties regarding the identification and characterisation of multiple bacterial and host factors critical to L. monocytogenes pathogenicity. It also briefly summarises some of the key findings from our laboratory on this topic over the past years.